Physical Properties of Durian (Durio zibethinus Murr) Seed Strach and its Associated Edible Film - Synodalia C. Wattimena; Philip J. Patty (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2025)
Starch has become a popular material as a substitute for conventional crude oil in plastic production. An edible film, a transparent thin film made from biobased materials, is one product that mostly uses starch. In this study, the starch of durian (Durio zibethinus Murr) fruit seed was used to make an edible film, and the physical properties of the starch and its associated edible film were characterized. A light microscope was used to observe the shapes and size distribution of the granules, a basic component of the starch consisting of linear amylose and branched amylopectin chains, and XRD spectroscopy was used to characterize the crystalline properties of the starch. Most of the granules were in spherical shapes with some irregularities, and the diameter ranged from 1.11 to 6.67 µm. Based on the XRD data, durian seed starch can be classified as a B-type starch with a crystallinity index of 22.2%. An edible film made from durian seed looks transparent brownish with dark brown spots. Its water vapor transmission rate was 2.49±0.01 g/m²hour, water absorption 145.1±34.9%, and water solubility 13.36±0.86%.